Hearing children in court disputes between parents - Mackay, Kirsteen (CRFR, 2013)
The Children (Scotland) Act 1995 gives children the right to have their views taken into account when their parents take a dispute over the child to court. This is consistent with Article 12 of the United Nations Convention of the Rights of the Child (UNCRC). The most common dispute concerning children which comes before the court is over the amount of contact a child should have with the non-resident parent. This briefing reports key findings from a recent study that examined court cases affecting just under 300 children. The research found that the majority of children do not have their views taken into consideration as part of the court process. When children’s views are heard, many struggle to be taken seriously if they do not wish to see their non-resident parent because of the conflict their decision has with the court’s assumption that contact with both parents is the best outcome for the child.
Keywords: Children and young people; Divorce and separation; Family policy and law; Abuse and violence